Social Representations Theory and Physical Education: Analysis of theses and dissertations defended in Brazilian post-graduation programs (Research, Society and Development, 2021)
This research focused on mapping and analyzing theses and dissertations defended between 2013 and 2020 in Brazilian post-graduation programs and are related to the social representations and Physical Education in educational context. With regards to methodological aspects, this investigation is characterized as a research of quali-quantitative approach with bibliographic design and bibliometric analysis. The search for the academic productions was made in the Brazilian Digital Platform of Theses and Dissertations and in Theses and Dissertations Catalogue by Capes throughout the descriptors “social representations” and “Physical Education”, utilizing the boolean operator AND. After the application of the inclusion and exclusion criteria, twenty-eight academic productions were selected to a deeper analysis. The results show that in recent years there has been greater adherence to the Social Representations Theory by Brazilian graduating students who research Scholar Physical Education. By the way, stands out that still is necessary a greater appropriation of this theory by the researchers in the area.